Ready, set, snow! - Klein, Abby; McKinley, John (New York : Blue Sky Press, 2009)
When Mrs. Wushy announces that the class will be competing in the mini-Winter Olympics, everyone is excited for the competition. But, after betting Max the bully that he will win the Snowshoe Race, Freddy heads straight for snowshoe boot camp, and fast! Will Freddy be able to win gold amid sled pulls and the infamous Snowball Toss?
Keywords: Sportsmanship -- Fiction; School fiction